Mr. and Mrs. Mark G. Norris 67th anniversary held (Raton, New Mexico Raton Range, 1881)
Newspaper Article on the 67th Anniversary of Virgal and Lorena Moore
Master list item #: 18
File location is in the Raton File Cabinet
Keywords: Norris, Mark; Norris, Mary; Bryant, Patricia; Norris, Jonathan J; Hickel, Doris; Stockton, Anita; Norris, Mark G. Jr; Hobbs, Jean; Menefee, Joan; Moore, Phyllis; Herron, Fern; Norris, Nathan P; Biography; Local History; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Maxwell, New Mexico; Estancia, New Mexico; Santa Rosa, California; Novato, California; Midland, Michigan; Ellensberg, Washington; Artisia, New Mexico; Odgen, Utah; Farmington, New Mexico; Carnation, Washington